Size Matters - Nanotechnology and Therapeutics in Rheumatology and Immunology - S. Henderson, Carl; C. Madison, Andrew; Shah, Ankoor (Current Rheumatology Reviews, 2014)
Nanotechnology, or the use of technology at the submicron scale, and its application to medicine (nanomedicine) draws from many ideas and technological advancements across myriad fields of materials technology and has improved biomedical understanding. Nanotechnology puts current materials science on the same physical scale as classic immune mediating substances, including viruses, moieties found on prokaryotic bacteria, and antigen presenting cells. Functionalized nanoparticles, fullerenes, liposomes, nanogels, and virus-like particles, are several examples of nanotechnology that are currently being applied to the treatment of oncologic and infectious diseases. However, the majority of the current commercial utilization of nanomedicine has been directed towards creating improved vaccines in order to prevent infectious diseases. These processes may have direct applications toward the creation of vaccines used to treat autoimmune disease as well. Current therapeutics utilizing nanotechnology, are gaining traction in treatments for gout and rheumatoid arthritis, and experimental animal models have demonstrated success in using the above technologies to improve the effectiveness and safety of current standard treatment of rheumatologic illnesses. Here we review many of the common forms of nanoparticles used in medical applications as well as where they have found a role in rheumatology. Continued technical feasibility, ongoing safety studies, and lingering questions on cost are all issues that have not yet been resolved in regards to widespread application in rheumatology and immunology.
Keywords: Immunology